Small-molecule targeting MuRF1 protects against denervation-induced diaphragmatic dysfunction: underlying molecular mechanisms - Ribeiro, Fernando; Jannig, Paulo R.; Labeit, Siegfried; Moriscot, Anselmo S. (Journal of cachexia, sarcopenia and muscle, 2025)
Background Mechanical inactivity rapidly induces diaphragm muscle fibres' contractile dysfunction and atrophy. Diaphragm weakness can impair respiratory function, quality of life and increase risks of morbidity and mortality. Muscle RING-finger protein-1 (MuRF1) expression is upregulated during denervation and muscle inactivity and is known to target key muscle proteins for degradation. We previously reported that the small-molecule targeting MuRF1 (MyoMed-205) protects against diaphragm contractile dysfunction and atrophy after 12 h of unilateral diaphragm denervation (UDD) in rats. In this study, we investigated the mechanisms by which MyoMed-205 protects the diaphragm structure and function during early UDD in rats. Methods Male Wistar rats were subjected to unilateral diaphragm denervation (UDD) for 12 h. Immediately after UDD, rats received either a placebo (vehicle) or small-molecule targeting MuRF1 (MyoMed-205, 50 mg/kg bw), and outcomes were compared with sham-operated controls. Diaphragm was used for histological, morphometric, transcriptomic (RNA-seq) and protein content (Western blot) analysis. Results UDD induced diaphragm slow- (Type I: p = 0.03) and fast-twitch (Type IIa: p = 0.04; Type IIb/x: p = 0.02) fibres atrophy after 12 h, which was prevented by MyoMed-205 (p < 0.05). Mechanistically, UDD perturbed mechanisms involved with myofibre ultrastructure and contractility, mitochondrial function, proteolysis and tissue remodelling in the diaphragm. MyoMed-205 enhanced the activation of mechanisms required for sarcomere integrity, calcium handling, antioxidant defence, chaperone-mediated unfolded protein response and muscle growth. MyoMed-205 also mitigated intramuscular fat deposition and pro-fibrotic responses triggered by UDD. Conclusions Small-molecule targeting MuRF1 (MyoMed-205) protects against diaphragm muscle contractile dysfunction and atrophy after 12 h of UDD. Herein, we demonstrate that this protective effect involved augmented activation of signalling pathways controlling muscle structure and function, chaperone-mediated unfolded protein and muscle growth, while mitigating intramuscular fat deposition and pro-fibrotic responses triggered by UDD at the transcriptional and/or protein level.
Erstmals veröffentlicht: 16. November 2025
Gesehen am 17.02.2026